Achievement Motivation Training (AMT) for Burnout - Abd Hamid Cholili (Jurnal KESANS : Kesehatan dan Sains, 2021)
A teaching profession is a form of human service profession that is full of challenges (Maslach & Jackson, 1986). Greenbreg & Baron (1995) stated that high job demands can lead to burnout. Pines and Aronson (1989) define burnout as physical, emotional, and mental exhaustion caused by long-term involvement in emotionally demanding situations. Burnout itself occurs because of three dimensions, namely emotional exhaustion, depersonalization, and decreased personal achievement so that high pressure at work can affect the three dimensions of Burnout. Sullivan (1989) explains that one of the factors that can affect burnout is motivation. Therefore, it is important for teachers to develop motivation in order to overcome the burnout problem they face, and one way to develop motivation is with Achievement Motivation Training (AMT). Achievement Motivation Training (AMT) is a training activity to increase the need for achievement in a person. The purpose of this study was to determine the effectiveness of Achievement Motivation Training (AMT) in reducing burnout with the hypothesis that Achievement Motivation Training (AMT) had an effect on reducing burnout. The sample of this study was 20 teachers at SMAI Miftahul Ulum Jatiurip Krejengan Probolinggo with details of 10 male teachers and 10 female teachers. Sampling in this study used a purposive technique, namely selecting samples according to the desired or with certain characteristics (Latipun, 2002). The method used to analyze the data in this research is a t-test. The t-test used is the Mann-Whitney test. Based on the hypothesis test from the analysis results obtained a significance value of 0.000. This means that there is an effect of Achievement Motivation Training (AMT) in reducing burnout. The results of the analysis also obtained the Mean Rank burnout of male and female teachers at the pretest time = 29.33 with the posttest value = 11.68. Based on this value, it can be concluded that giving an intervention using Achievement Motivation Training can reduce Burnout. From these results, it can be concluded that the provision of Achievement Motivation Training (AMT) can reduce burnout experienced by teachers at SMAI Miftahul Ulum Jatiurip Krejengan Probolinggo.